Islamic Education in Law No. 28 of 2003 about the National Education System - Wahyu Ramadhan; Abd Mukti; Sapri Sapri (Edumaspul: Jurnal Pendidikan, 2024)
This scientific study aims to analyze in more depth related to Islamic education in Law no. 20/2003. This scientific study uses qualitative research methods with a historical approach. The data used in this study is secondary data, including books and journals that are appropriate to the topic studied. The results of the analysis state that Islamic education is not only a means of transferring knowledge and developing basic human potential but also an actualization of Islamic values ​​so that we can be free from ignorance. This is supported by Law no. 20/2003, which bridges Islamic educational institutions (madrasas) to be able to contribute directly to efforts to educate the nation's life. Madrasas have been given a strategic position as a form of formal educational institution recognized by the Indonesian government, on a par with other formal educational institutions. Even Law No. 20/2003 also gives extraordinary existence to Islamic education as a mandatory subject in primary, secondary, and higher education